Evaluation of Clove Phytochemicals as Potential Antiviral Drug Candidates Targeting SARS-CoV-2 Main Protease: Computational Docking, Molecular Dynamics Simulation, and Pharmacokinetic Profiling - Chandra Manivannan, Arun; Malaisamy, Arunkumar; Eswaran, Murugesh; Meyyazhagan, Arun; Arumugam, Vijaya Anand; Rengasamy, Kannan R. R.; Balasubramanian, Balamuralikrishnan; Liu, Wen-Chao (Frontiers in Molecular Biosciences, 2022)
The SARS-CoV-2 virus can cause a sudden respiratory disease spreading with a high mortality rate arising with unknown mechanisms. Still, there is no proper treatment available to overcome the disease, which urges the research community and pharmaceutical industries to screen a novel therapeutic intervention to combat the current pandemic. This current study exploits the natural phytochemicals obtained from clove, a traditional natural therapeutic that comprises important bioactive compounds used for targeting the main protease of the SARS-CoV-2. As a result, inhibition of viral replication effectively procures by targeting the main protease, which is responsible for the viral replication inside the host. Pharmacokinetic studies were evaluated for the property of drug likeliness. A total of fifty-three bio-active were subjected to the study, and four among them, namely Eugenie, Syzyginin B, Eugenol, and Casuarictin, showed potential binding properties against the target SARS-CoV-2 main protease. The resultant best bioactive was compared with commercially available standard drugs. Further, validation of respective compounds with a comprehensive molecular dynamics simulation was performed using Schrödinger software. To further validate the bioactive phytochemicals and delimit the screening process of potential drugs against COVID-19 disease, in vitro and in vivo clinical studies are needed to prove their efficacy.